Effectiveness of E-Archives As A Media Of Information Technology Based Data Management In Universitas Lancang Kuning - Bayu Febriadi; Adi Rahmat (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2020)
Badan Penjaminan Mutu of Universitas Lancang Kuning (BPM UNILAK) is an agency that is tasked with organizing an internal quality assurance system (SPMI) and an external quality assurance system (SPME) or what is also known as accreditation, but in managing documents related to SPMI data and accreditation not yet There are information technology-based media that can be utilized in the implementation of these activities, while BPM UNILAK has implemented information technology in daily activities so that there are problems with delays in data presentation, missing data, this, of course, affects the performance of the Quality Assurance Agency and is inefficient in presenting information that is needed at any time and the importance of this activity is very high in building a quality culture at Universitas Lancang Kuning. To answer these problems, it is necessary to have an information technology-based document filing system that can process data more quickly, precisely and integrated to make it better in presenting the information. The methods used in this study include system requirements analysis, system design, implementation and testing and system maintenance. With the use of information technology in the application of computerized-based applications for archiving and presenting accreditation data needs, it is hoped that it can help the academic community more quickly and accurately in processing accreditation instrument data. It is hoped that with the development of archiving applications and the presentation of accreditation instruments by completing the System Development Lyfe Cycle (SDLC) method in the problem analysis stage, the applications built can improve the quality of filling accreditation instruments in data processing that are well integrated and can be used at any time by the community. Universitas Lancang Kuning academics.